Faktor-faktor Menentukan Harga Saham Syariah Pada Daftar Saham Terdaftar di Index Saham Syariah Indonesia - Jamaluddin Majid,; Gagaring Pagalung,; Andi Ruslan, (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2022)
This study aims to determine the effect of Return On Assets (ROA), Earning Per Share (EPS), Debt to Equity Ratio (DER) and Return On Equity (ROE) on stock prices in Islamic trading and investment services companies listed on the Index. Indonesian Sharia Shares. This study uses secondary data with quantitative methods that connect the dependent variable with the independent variable using the SPSS program. The population of this study are companies in the Islamic trading and investment services sector listed on the Indonesian Sharia Stock Index (ISSI). The sample used as many as 11 companies with purposive sampling method obtained according to the criteria. The results of the analysis show that Return on Assets (ROA) has a significant and positive effect on stock prices in the company. Meanwhile, the Earning Per Share (EPS) and Debt to Equity Ratio (DER) variables have no significant effect on the company's stock price. While the Return On Equity (ROE) variable has a significant and negative effect on stock prices in sharia trading and investment service sector companies listed on the Indonesian Sharia Stock Index.